Identity (de)construction, classroom challenges and roles assumed by non-native English-speaking teachers in Colombia - Tarazona Ariza, Silvia Andrea (Rastros Rostros, 2021)
Introduction. This article aims to explore personal and professional aspects such as the construction of identity, the frequent challenges in classrooms in the public sector, and the roles that non-native speaker teachersof English assume (and are granted by others), on a daily basis, in a context that is highly influenced by native-speakerism and colonizing views toward English across the global south.Methodology. This research is qualitative and exploratory. For the data collection process, teachers’ personalnarratives, semi-structured interviews as well as a focal group session were conducted. The participants ofthis research were five teachers of English as a foreign language from different regions of Colombia, who donot know each other and who are ascribed to the public sector of education.Findings. Results reveal that non-native speaker teachers of English in Colombia usually feel compared tonative speakers of English and overlooked in their job settings. Likewise, other problematic issues such as thesocio-cultural context of students, as well as the lack of resources in public school come to light in this study.Conclusions: Non-native Speaker English teachers in Colombia are not perceived as a valid linguistic model tofollow and this situation leads to the development of a professional identity crisis among teachers since theyare not clear about their relevance as trained professionals in the field of Language Education.
Keywords: native-speakerism; EFL teachers; identity; linguistic colonialism; teacher’s roles in the classroom